PERENCANAAN STRATEGIS SISTEM DAN TEKNOLOGI INFORMASI PADA CV DELTA RAYA MENGGUNAKAN METODE WARD AND PEPPARD - Handoko, Febrian; Setyawan, Henry Bambang; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
CV Delta Raya is a manufacturing company engaged in the production of indoor type furniture, both for home and office purposes. CV Delta Raya has several problems, including investments that do not support business objectives, lack of control over meeting IS / IT needs, never do IS / IT planning for the future, and do not have good information management. With the current problems that exist, CV Delta Raya needs to carry out System and Information Technology Strategic Planning. System and Information Technology strategic planning will be based on the Ward and Peppard method, in the process it will do planning based on business needs, which will produce the company's business strategy, Business IS Strategies that produce SI solutions for the company's business strategy, IS / IT Management Strategies to form resources that competent in carrying out strategic planning projects, IT Strategy that produces infrastructure and platforms so that business solutions can run optimally and Future Application Portfolios that will be a reference in future Information Systems and Technology development so that information systems and technology can improve processing company information and provide better service for company partners.